Studies on the genus Lefroyothrips, with new records from Malaysia, New Caledonia and a new species from Australia (Thysanoptera, Thripidae) - Mound, L.a.; Ng, Y.f. (Zootaxa, 2021)
Six species are recognised in the genus Lefroyothrips, including one new species from Australia. The metascutal chaetotaxy of two of these species is unique amongst Thripidae. New distribution records given here indicate that four of the species are widely distributed: L. pictus across tropical Africa, L. lefroyi from northern India to Taiwan, L. fasciatus from Malaysia to northern Australia and New Guinea, and L. varatharajani from southern India to New Caledonia and northern Australia. An illustrated key is provided to the six known species in this genus.